Evolutionary Remodeling of the Cell Envelope in Bacteria of the Planctomycetes Phylum. (6th August 2020) - Mahajan, Mayank; Seeger, Christian; Yee, Benjamin; Andersson, Siv G E
Abstract: Bacteria of the Planctomycetes phylum have many unique cellular features, such as extensive membrane invaginations and the ability to import macromolecules. These features raise intriguing questions about the composition of their cell envelopes. In this study, we have used microscopy, phylogenomics, and proteomics to examine the composition and evolution of cell envelope proteins in Tuwongella immobilis and other members of the Planctomycetes . Cryo-electron tomography data indicated a distance of 45 nm between the inner and outer membranes in T. immobilis . Consistent with the wide periplasmic space, our bioinformatics studies showed that the periplasmic segments of outer-membrane proteins in type II secretion systems are extended in bacteria of the order Planctomycetales . Homologs of two highly abundant cysteine-rich cell wall proteins in T. immobilis were identified in all members of the Planctomycetales, whereas genes for peptidoglycan biosynthesis and cell elongation have been lost in many members of this bacterial group. The cell wall proteins contain multiple copies of the YTV motif, which is the only domain that is conserved and unique to the Planctomycetales. Earlier diverging taxa in the Planctomycetes phylum contain genes for peptidoglycan biosynthesis but no homologs to the YTV cell wall proteins. The major remodeling of the cell envelope in the ancestor of the Planctomycetales coincided with the emergence of budding and other unique cellular phenotypes. The results have implications for hypotheses about the process whereby complex cellular features evolve in bacteria.